Overexpression of EMMPRIN isoform 2 is associated with head and neck cancer metastasis. - Zhiquan Huang; Ning Tan; Weijie Guo; Lili Wang; Haigang Li; Tianyu Zhang; Xiaojia Liu; Qin Xu; Jinsong Li; Zhongmin Guo (PLoS ONE)
Extracellular matrix metalloproteinase inducer (EMMPRIN), a plasma membrane protein of the immunoglobulin (Ig) superfamily, has been reported to promote cancer cell invasion and metastasis in several human malignancies. However, the roles of the different EMMPRIN isoforms and their associated mechanisms in head and neck cancer progression remain unknown. Using quantitative real-time PCR, we found that EMMPRIN isoform 2 (EMMPRIN-2) was the only isoform that was overexpressed in both head and neck cancer tissues and cell lines and that it was associated with head and neck cancer metastasis. To determine the effects of EMMPRIN-2 on head and neck cancer progression, we transfected head and neck cancer cells with an EMMPRIN-2 expression vector and EMMPRIN-2 siRNA to exogenously modulate EMMPRIN-2 expression and examined the functional importance of EMMPRIN-2 in head and neck cancer invasion and metastasis. We found that EMMPRIN-2 promoted head and neck cancer cell invasion, migration, and adhesion in vitro and increased lung metastasis in vivo. Mechanistic studies revealed that EMMPRIN-2 overexpression promoted the secretion of extracellular signaling molecules, including matrix metalloproteinases-2(MMP-2), urokinase-type plasminogen activator(uPA) and Cathepsin B, in head and neck cancer cells. While MMP-2 and uPA have been demonstrated to be important mediators of EMMPRIN signaling, the role of Cathepsin B in EMMPRIN-mediated molecular cascades and tumorigenesis has not been established. We found that EMMPRIN-2 overexpression and Cathepsin B down-regulation significantly inhibited the invasion, migration and adhesion of Tca8133 cells, suggesting that Cathepsin B is required for EMMPRIN-2 enhanced cell migration and invasion in head and neck cancer. The results of our study demonstrate the important role of EMMPRIN-2 in head and neck cancer progression for the first time and reveal that increased extracellular secretion of Cathepsin B may be a novel mechanism underlying EMMPRIN-2 enhanced tumor progression in head and neck cancer.